Sexual Dysfunction Related to Psychotropic Drugs: A Critical Review. Part III: Mood Stabilizers and Anxiolytic Drugs - La Torre, A.; Giupponi, G.; Duffy, D. M.; Pompili, M.; Grözinger, M.; Kapfhammer, H. P.; Conca, A. (Pharmacopsychiatry, 2014)
Sexual dysfunction is a potential side effect of mood stabilizers and anxiolytic drugs: this article presents a critical review of the current literature. Although many studies have been published on sexual side effects of psychopharmacological treatment, only a minority relate to mood stabilizers and anxiolytic drugs. Most of these studies are not methodologically robust, few are RCTs and most did not use a validated rating scale to evaluate sexual functioning. In addition, many of the studies on sexual dysfunction associated with mood stabilizers and anxiolytic drugs are limited by other methodological flaws. While there is evidence to suggest that mood stabilizers, with some exceptions, negatively affect sexual functioning, there is still insufficient evidence to draw any clear conclusions about the effects of anxiolytic drugs on sexual function. There is some weak evidence to indicate that switching from enzyme-inducing to non-enzyme-inducing anticonvulsant drugs, could be clinically useful. Some researchers recommend that sexual dysfunction in patients taking antiepileptic drugs should in general be treated according to standard guidelines for the management of sexual dysfunction, since reliable data on special populations is not available. However, specific approaches may be useful, but cannot yet be recommended until further validating research has been conducted. We did not find evidence supporting the use of any specific treatment strategy for sexual dysfunction associated with anxiolytic treatment.This study was conducted in 2013 using the paper and electronic resources of the library of the Azienda Provinciale per i Servizi Sanitari (APSS) in Trento, Italy (http://atoz.ebsco.com/Titles/2793). The library has access to a wide range of databases including DYNAMED, MEDLINE Full Text, CINAHL Plus Full Text, The Cochrane Library, Micromedex healthcare series, BMJ Clinical Evidence. The full list of available journals can be viewed at http://atoz.ebsco.com/Titles/2793, or at the APSS web site (http://www.apss.tn.it). In completing this review, a literature search was conducted using the key words “anxiolytic drugs”, “mood stabilizers”, “benzodiazepines”, “psychotrophic drugs”, “sexual dysfunction”, “sexual side effects”, “treatment-emergent sexual dysfunction”. All resulting listed articles were reviewed.This review includes studies that investigated the relationship between mood stabilizer and anxiolytic drug treatment and sexual dysfunction. The purpose was to identify possible intervention strategies for sexual dysfunction related to these drugs.
Keywords: anxiolytic drugs; mood stabilizers; benzodiazepines; psychotropic drugs; sexual dysfunction; sexual side effects; treatment-emergent sexual dysfunction